Giibinenimidizomin: Owning Ourselves - Critical Incidents in the Attainment of Aboriginal Identity - Goodwill, Alanaise O.; McCormick, Rod (Canadian Journal of Counselling and Psychotherapy, 2011)
This research explored the facilitation and hindrance of Aboriginal identity attainment and developed a scheme of categories to describe what facilitates and hinders cultural identity among Canadian Aboriginal adults living in British Columbia. Twelve individuals, interviewed using the critical incident technique, were asked to describe observable events that they thought had significantly helped or hindered their Aboriginal identity. In total, 114 helping incidents and 24 hindering incidents were identified. Helping incidents were placed into 12 categories (Participating in a Cultural Gathering, Participating in a Group of Aboriginal People, Connecting with Family, Changing Self-Perception, Helping Other Aboriginal People, Verbalizing Experiences as an Aboriginal Person, Spiritual Experience, Getting Support from Parents, Attending a Cultural Gathering, Being Influenced by a Grandparent, Personal Accomplishment, and Experiencing Positive Representations of Aboriginals). Hindering incidents were placed into 3 categories (Living with Separation from Aboriginal Peoples/Culture, Experiencing Racism and Prejudice, and Experiencing Negative Portrayals of Aboriginals). Ad hoc analyses supported the trustworthiness of the proposed categorical system. The results support the perspective of the dominant literature, while suggesting future directions for research and practice in multicultural counselling with respect to Aboriginal cultural identity.